(untitled) (Research, Society and Development, 2021)
The objective was to identify the development of Hand-Foot Syndrome in the literature, as an adverse effect of the use of chemotherapy. Integrative review performed in LILACS, BDENF, PubMed and ScienceDirect databases, in Portuguese, English and Spanish. Clinical trials published with a time frame from 2016 to 2021 centered on the adult audience were selected and segregated into two topics. The information was tabulated in Microsoft Excel® 2010 program and processed based on the strategy: simple descriptive arithmetic mean, absolute and relative frequency. A total of 559 articles were found, after applying the inclusion and exclusion criteria, 20 studies were chosen to compose the final sample. The pharmacological class most listed as a potentiator of SMP was fluoropyrimidines (80%). Through the clinical manifestations presented in the syndrome, negative impacts perpetuate the routine of patients, as the performance of activities of daily living is compromised, to minimize the damage caused by this condition, therapeutic methods were highlighted, these are applied to reduce the degrees of the syndrome and better quality of life. In summary, it is clear that the use of chemotherapy increases overall and disease-free survival, however it causes some recurrent adverse reactions, including the Hand-Foot Syndrome, its manifestations are not life-threatening, but the limitations triggered infer damages to the self-care and quality of life becomes unsatisfactory.